Small Structure, Large Effect: Functional Surfaces Inspired by Salvinia Leaves. Issue 9 (14th September 2021) - Bing, Wei; Wang, He; Tian, Limei; Zhao, Jie; Jin, Huichao; Du, Wenbo; Ren, Luquan
Abstract : Functional Surfaces Inspired by Salvinia Leaves Recent findings from the aquatic plant Salvinia provide novel approaches for the application of superhydrophobic surfaces. In article number 2100079, Limei Tian, Huichao Jin, and co‐workers summarize the recent developed advanced techniques for duplicating the complex eggbeater structures of Salvinia leaves. The review also discusses the engineering applications and future development of Salvinia ‐inspired surfaces.